Prognostic value of proadrenomedullin in patients with COVID-19 pneumonia - Astapovskii, Aleksandr A.; Drozdov, Vladimir N.; Shikh, Evgenia V.; Melkonyan, George G.; Sizova, Zhanna M.; Zakharova, Valeria L.; Shindryaeva, Natalia N.; Lapidus, Natalia I. (Frontiers in Medicine, 2022)
Objective: The aim of the study was to assess the role of mid-regional proadrenomedullin (MR-proADM) in comparison with routine laboratory tests in patients with COVID-19. Materials and Methods: 140 hospitalized patients aged 18 and older with COVID-19 pneumonia were included in prospective single-center study. Routine analyses were performed as well as MR-proADM level was measured within the first and the third hospital days using Human MR pro-ADM (Mid-regional pro-adrenomedullin) ELISA Kit with a sensitivity of 0.469 pmol/ml (immunofluorescence assay). National Early Warning Score (NEWS) was used for primary assessment of the disease severity. The groups had no statistically significant difference in sex, comorbidity, body temperature, oxygen saturation level, heart rate, respiratory rate, and levels of C-reactive protein (CRP) level and procalcitonin (PCT). The deceased patients had statistically significant difference in age (median, 76 years; interquartile range, 73.2-78.2 vs median, 66 years; interquartile range, 62-67; p <0.0001), NEWS value (median, 5; interquartile range, 3- 8 vs median, 2; interquartile range, 0-6; p <0.05), hospitalization period (median, 17; interquartile range, 7-35 vs median, 6; interquartile range, 3-14), quantitative CT extent of lung damage > 50% (n = 26 (86.7%) vs n = 9 (8.2%) p <0.0001), level of leukocytes (median, 11.4 x109/L; interquartile range, 6.2-15.5 vs median, 5.3 x109/L; interquartile range, 4.7-6.4; p = 0.003), level of neutrophils (median, 80.9%; interquartile range, 73.6-88.6 vs median, 72.6%; interquartile range, 68.7-76.9; p = 0.027), level of MR-proADM at the first hospital day (median, 828.6 pmol/ml; interquartile range, 586.4-1184.6 vs median, 492.6 pmol/ml; interquartile range,